2018
DOI: 10.1002/jcp.27406
|View full text |Cite
|
Sign up to set email alerts
|

miR‐335‐5p induces insulin resistance and pancreatic islet β‐cell secretion in gestational diabetes mellitus mice through VASH1‐mediated TGF‐β signaling pathway

Abstract: Multiple studies have reported different methods in treating gestational diabetes mellitus (GDM); however, the relationship between miR-335-5p and GDM still remains unclear. Here, this study explores the effect of miR-335-5p on insulin resistance and pancreatic islet β-cell secretion via activation of the TGFβ signaling pathway by downregulating VASH1 expression in GDM mice. The GDM mouse model was established and mainly treated with miR-335-5p mimic, miR-335-5p inhibitor, si-VASH1, and miR-335-5p inhibitor + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Following a 12 h fasting period, mice were anesthetized with isoflurane. Blood samples were collected by eyeball extirpation and then centrifuged at 3000 rpm for 15 min to obtain the serum (−20 °C storage). After taking the blood samples, the mice were sacrificed by cervical dislocation .…”
Section: Methodsmentioning
confidence: 99%
“…Following a 12 h fasting period, mice were anesthetized with isoflurane. Blood samples were collected by eyeball extirpation and then centrifuged at 3000 rpm for 15 min to obtain the serum (−20 °C storage). After taking the blood samples, the mice were sacrificed by cervical dislocation .…”
Section: Methodsmentioning
confidence: 99%
“…Effects of fluoxetine on lipid metabolism in rats with STZ-induced diabetes. numerous pathways are involved in the development of diabetes, including insulin secretion, insulin signaling, glycolysis and lipid metabolism (19,17). To investigate the extent of lipid metabolism, the expression levels of associated proteins were evaluated in rats.…”
Section: Resultsmentioning
confidence: 99%
“…no. JCSW2610) provided by Shanghai Jichun Industrial Co., Ltd. Insulin resistance was estimated using a homeostasis model, as described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence indicating the high potential of miRNAs as biomarkers for complex diseases [28], [52]- [60]. Among the miRNA post-transcriptional regulators of the identified DEGs, it has been shown that mir-335-5p increases insulin resistance and suppresses pancreatic Κ cell secretion [61]. Moreover, overexpression of mir-335-5p can perturb insulin secretion [62].…”
Section: Discussionmentioning
confidence: 99%